Breaking news : why media matters - Delisle, Raina (Orca think, 2023)
"This just in: Becoming a savvy news consumer is more important than ever! People are spending more time on the internet, where they're exposed to fake news and clickbait. And as major news events such as the COVID-19 pandemic have shown us, the spread of misinformation puts lives at risk. Breaking News: Why Media Matters explores the history of the media industry, the important role it plays today and the challenges it faces. It also gives kids the tools they need to tell fact from fiction and find the news they can use." -- Back cover.